p=10/3 or 3.33333333333333333333333333333333333333333333333333333333333333333333333333333
We're guessing that what you really want to know is the value of 'p'that makes the statement true. Here's how to find it:3p + 4 = -14Subtract 4 from each side:3p = -18Divide each side by 3:p = -6
plus For example: (+15) + (+1) = +16 or 16 But minus plus minus is equals to minus itself For example: (- 8) - (- 4) = - 4
This expression when simplified comes to: 0
you cant unless you know what the value of P equals
3p + 4p +10 = 5p + 2 Subtracting 5p from both sides: 3p + 4p - 5p + 10 = 5p + 2 - 5p ie 2p + 10 = 2 Subtract 10 from both sides: 2p + 10 - 10 = 2 - 10 ie 2p = -8 Divide both sides by 2: p = -4
==>-3p+7=5-8p+6 ==>5p+7=11 ==>5p=4 ==>p=4/5
3p +12= 7p 7p-3p=12 12?3=4 p=4
We're guessing that what you really want to know is the value of 'p'that makes the statement true. Here's how to find it:3p + 4 = -14Subtract 4 from each side:3p = -18Divide each side by 3:p = -6
8-3p-4 = 2p 4 - 3p = 2p add 3p to both sides 4 = 5p divide both sides by 5 4/5 = p
plus For example: (+15) + (+1) = +16 or 16 But minus plus minus is equals to minus itself For example: (- 8) - (- 4) = - 4
3p + 18 = 5p + 4Subtract 4 from both sides3p + 14 = 5pSubtract 3p from both sides14 = 2pDivide both sides by 27 = pNote : For presentation purposes the unknown or variable is normally put as the subject of the equation. The answer is then presented as p = 7.
100 - 3p = 88 -3p = 88 - 100 -3p = -12 p= (-12/-3) p = 4 so 100 - 3 * 4 = 88
This expression when simplified comes to: 0
you cant unless you know what the value of P equals
4p + 9 - 7p + 2 4p - 7p + 9 + 2 p(4 - 7) + 9 + 2 -3p + 11
3p + 4p +10 = 5p + 2 Subtracting 5p from both sides: 3p + 4p - 5p + 10 = 5p + 2 - 5p ie 2p + 10 = 2 Subtract 10 from both sides: 2p + 10 - 10 = 2 - 10 ie 2p = -8 Divide both sides by 2: p = -4
If p = 7 then 3p must equal 21. So 21 - 25 = -4 and -4 divided by 2 = -2